2020
DOI: 10.3390/min10080670
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical, Mineralogical, and Chemical Characterisation of Cretaceous–Paleogene/Neogene Kaolins within Eastern Dahomey and Niger Delta Basins from Nigeria: Possible Industrial Applications

Abstract: The demand for kaolinitic clays for various industrial applications is increasing globally. The present study evaluated the potential industrial applications of kaolins from the Eastern Dahomey and Niger Delta Basins, Nigeria. The colour, pH, electrical conductivity (EC), particle size distribution (PSD), plastic limits and liquid limits of the kaolins were determined. Mineralogical properties were assessed using X-ray diffractometry (XRD), scanning electron microscopy (SEM), and differential thermal analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…According to Daoudi et al (2014), higher clay and silt fractions usually give rise to relatively higher plasticity. The higher clay and silt fractions as recorded in the studied ISQW may likely be responsible to the relatively higher plasticity; an indication of material with likely high potential to swelling (Oyebanjo et al 2020). Raw materials with PI (7<PI<10) have low plasticity, and are not considered appropriate for use in building-related ceramics production as they would require addition of polymer in order to obtain adequate plastic behavior to avoid cracking during extrusion (Bain 1971;Dondi et al 2002;Oyebanjo et al 2020;Boukoffa et al 2021).…”
Section: Physical Characteristics Of the Indurated Shalementioning
confidence: 92%
See 3 more Smart Citations
“…According to Daoudi et al (2014), higher clay and silt fractions usually give rise to relatively higher plasticity. The higher clay and silt fractions as recorded in the studied ISQW may likely be responsible to the relatively higher plasticity; an indication of material with likely high potential to swelling (Oyebanjo et al 2020). Raw materials with PI (7<PI<10) have low plasticity, and are not considered appropriate for use in building-related ceramics production as they would require addition of polymer in order to obtain adequate plastic behavior to avoid cracking during extrusion (Bain 1971;Dondi et al 2002;Oyebanjo et al 2020;Boukoffa et al 2021).…”
Section: Physical Characteristics Of the Indurated Shalementioning
confidence: 92%
“…However, the concentration of Fe 2 O 3 was not regarded as the only factor related to colouration of ceramic products. The presence of TiO 2 along with Fe 2 O 3 , according to Diko-Makia and Ligege (2020) and Oyebanjo et al (2020), can be associated with discoloring components such as hematite, geothite and anatase minerals. Keller (1968) and Oyebanjo et al (2020) described raw materials containing both TiO 2 and Fe 2 O 3 ≥ 3.0 wt% as useless to the ceramist as Fe 2 O 3 concentration of < 2.0 wt% is considered desirable especially for roo ng tiles manufacture (Zeballos et al 2016).…”
Section: Mineralogy and Chemical Characteristics Of The Indurated Shalementioning
confidence: 97%
See 2 more Smart Citations
“…From the result obtained from the study, it was seen that there are five major clay minerals namely, kaolinite, illite, smectite, and chlorite alongside proportions of mixed-layer (illite/smectite), while major oxide analysis indicated significant concentrations of SiO 2 , AI 2 O 3 , Fe 2 O, CaO, Na 2 O, K 2 O and MgO and that diagenesis of the clays resulted in the occurrence of alternating sequences of sandstones/shales. [31] evaluated the mineralogical, physicochemical (Ec, pH and PSD) and chemical charactertics of clay in parts of Eastern Dahomey and Niger Delta Basins, Nigeria using X-ray, SEM and DTA methods. From their findings it was observed that the clays have low Ec and pH values.…”
Section: Literature Review On Clay Mineral Across Southern Part Of Nigeriamentioning
confidence: 99%